3+6h=2h+14

Simple and best practice solution for 3+6h=2h+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+6h=2h+14 equation:


Simplifying
3 + 6h = 2h + 14

Reorder the terms:
3 + 6h = 14 + 2h

Solving
3 + 6h = 14 + 2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-2h' to each side of the equation.
3 + 6h + -2h = 14 + 2h + -2h

Combine like terms: 6h + -2h = 4h
3 + 4h = 14 + 2h + -2h

Combine like terms: 2h + -2h = 0
3 + 4h = 14 + 0
3 + 4h = 14

Add '-3' to each side of the equation.
3 + -3 + 4h = 14 + -3

Combine like terms: 3 + -3 = 0
0 + 4h = 14 + -3
4h = 14 + -3

Combine like terms: 14 + -3 = 11
4h = 11

Divide each side by '4'.
h = 2.75

Simplifying
h = 2.75

See similar equations:

| X/5-8=3 | | (x-5)/10=10/3 | | 6x+10=31 | | (y+12)+(y-18)=180 | | 15.4+d=23 | | -4y-6=-3y-8 | | 8x=6(x-1) | | 565.2=1/3.22/7.6.6.h | | 8x^2+44x+60= | | 5x+4=46-2x | | 7+3=-5(3x-2) | | 7-2h=15-5h | | 45/w=5 | | 6x+100=10x-8 | | 1/4(11-8)=3/4 | | -8(2t+9)=-72 | | -8(2t+9)=-72t | | -5(f-67)+74=-1 | | 3m+4=7-3m | | 0=3x^3-12 | | -2(-2x-7)=30 | | 20/k=4 | | h(t)=-16t^2+15t+5 | | 8x^2+44+60= | | 3r+54=10r+15 | | 4=b-2/3 | | 10z-z=-1+2z-2-4 | | 8+7a=5a | | Er+54=10r+15 | | -2/z=-1 | | 5y-(11-y)+12= | | 5y^2=5 |

Equations solver categories